Impact of higher concentration of Fe2O3 nanoparticles in biowick material and the influence of higher mass flow rate on a passive inclined solar still desalination - a sustainable approach - Pitchaiah Sudalaimuthu; Ravishankar Sathyamurthy; Mahmoud S. El-Sebaey (Results in Engineering, 2025)
This research integrates biowick materials modified with iron oxide (Fe2O3) nanoparticles to improve the freshwater yield of inclined solar stills (ISS) markedly, constituting a novel biotechnological application. The water mass flow rates of 0.29, 0.45, 0.75, and 1.3 kg/min were combined with two concentrations of nanoparticle (1% and 5% by weight) to study the ISS thermal performance, yield, and efficiency. Functionalization of jute cloth biowick with Fe2O3 nanostructures was proven to enhance solar absorption, water temperature, and evaporation rates. Under the lowest flow rate of 0.29 kg/min, the average water temperatures reached 67∘C for bare ISS, 69∘C with plain biowick, and 74∘C with 5% Fe2O3-functionalized biowick, yielding 1.60, 2.30, and 2.96 kg/m2 of freshwater daily. Thermal efficiency also showed improvement, from 25.25% for bare ISS to 51.85% with 5% Fe2O3 biowick, while exergy efficiency improved from 1.29% to 2.8%. Although increased mass flow rates typically lowered water yield due to reduced dwell time and thermal retention, the enhanced capillary action and thermal conductivity of the biowick mitigated this decline. The biowick modified with Fe2O3 exhibited an evaporative heat transfer coefficient increase of 28.7%–55.3%, confirming the improvement in the heat and mass transfer performance. From an economic perspective, the model with 5% Fe2O3-functionalized biowick attained a cost efficiency of $0.0106 per liter while achieving the shortest payback period of 101 days, even with the increased expenditure on nanoparticles. Analytical modeling using Response Surface Methodology (RSM) further validated the experimental findings, establishing high-accuracy predictive equations for water temperature and yield (R2 >0.95). This study focuses on the materials used in construction to demonstrate how greatly they impact the effectiveness of solar-powered desalination on a large scale while maintaining inexpensive and minimal ecological impact water purification systems.